Theoretical and Practical Foundations of the Development of Students’ Speech Through Lexemes Representing Color in Primary-Grade Mother Tongue Classes - Abdullazizova Rokhatoy Usmonaliyevna (Academia One, 2023)
one of the primary tasks of secondary education in this article is the formation of a positive attitude in students to the knowledge of the mother tongue, which is the main indicator of national culture and one of the important factors of personal development, as well as the main language of communication. There is also information about the main task of teaching the mother tongue in primary grades to develop students' speech, to enrich it with units of the language system at all levels, and above all to increase children's vocabulary
Keywords: worldview; communicative competence; linguistic personality